Approche des espaces de la pratique nautique par l’analyse de la fréquentation : l’exemple du bassin de navigation arcachonnais - Nicolas Le Corre; Solenn Le Berre; Ingrid Peuziat; Louis Brigand; Julien Courtel (VertigO)
Since the 1960s, pleasure-boating has experienced a significant development throughout the French coast. Although the harbor infrastructures are well studied, this is not the case of the recreational boater behaviors and distribution once on the water or on the nearby islands. This knowledge is, however, essential in order to improve and develop new integrated coastal planning strategies. This article presents the methodological framework of a recreational boating monitoring study conducted in the Arcachon Basin (France) between 2008 and 2009. The results further our understanding of this boating area that is based on different practice places.